2007
DOI: 10.1103/physrevb.76.245105
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrogen absorption on low-energy electronic collective excitations in palladium

Abstract: A theoretical study of electronic excitation spectra in Pd and PdH is reported. The calculations were performed with full inclusion of the electron band structure obtained within self-consistent pseudopotential approach. We demonstrate that the complicated Pd electronic structure at the Fermi level is reflected in a numerous peak structure of the excitation spectra. The evolution of the energy-loss spectrum with momentum and its anisotropy are analyzed. Strong modification of the excitation spectra upon hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 43 publications
0
19
0
1
Order By: Relevance
“…The oscillation scales are being commensurable with the lattice parameter (typically, ∼ 0.3-0.4 nm). As a result, as authors supposed [20,37], the correspondent acceleration of D + could lead to enhance of DD-reaction yield even for a low energy deuteride excitation.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 95%
See 2 more Smart Citations
“…The oscillation scales are being commensurable with the lattice parameter (typically, ∼ 0.3-0.4 nm). As a result, as authors supposed [20,37], the correspondent acceleration of D + could lead to enhance of DD-reaction yield even for a low energy deuteride excitation.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 95%
“…This is one of the number of models which are developing to explain the possible so-called low energy nuclear reactions (LENR) at deuterium-loaded Pd ( see review [36]). Recent theoretical study [37] and calculations [20] have shown that the excitation of the hydrogen subsystem (which leads to desorption of H,D) as a result of the electron bombardment is stipulated by the generation of plasma oscillations in the crystalline lattice, which are localized preferentially in the vicinity of hydrogen (deuterium) atoms. This process results in the electron-density oscillations and in the appearance of strong electric fields (∼ 10 8 V/cm) in the volume and on the plane of the hydride.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…The profile of Im[ϵ −1 ] is dominated by a broad feature whose energy smoothly shifts from ω P ≈ 7.7 eV for x = 0 to ω P ≈ 4.3 eV for x = 1. This peak is commonly attributed to the bulk plasmon although interband electron-hole pair transitions contribute to the weight as well [27]. Increasing the concentration of H in bulk PdH x shrinks the width of the plasmon peak and reduces its weight, due to the reduction in the density of states at the Fermi level and the increasing importance of interband electron-hole pair transitions.…”
Section: Resultsmentioning
confidence: 99%
“…Technical details of the first-principles calculations are similar to those used for Pd and PdH in Reference [27] and are only briefly summarized here. Density functional theory (DFT) is used to obtain the ground state of bulk PdH x for different values of x.…”
Section: Theorymentioning
confidence: 99%